Poyphenols – between neuroprotection and neurotoxicity - Lea POGAČNIK; Rui F.M. SILVA (Acta Agriculturae Slovenica, 2020)
Polyphenols are a group of secondary metabolites found in a wide variety of foods, such as fruits, vegetables, wine, tea, olive oil and chocolate. These compounds, in addition to their antioxidant activity, also possess strong anti-inflammatory properties. Numerous studies have therefore confirmed their potential role in preventing and treating various pathological conditions associated with oxidative stress and inflammation. Among these, the most prevalent ones include cancer, cardiovascular and neurodegenerative diseases, which globally represent one of the main causes of death and are therefore a major social and financial burden,  Numerous studies have clarified some of the mechanisms of action of polyphenols as antioxidant and anti-inflammatory compounds and have clarified their role in treatment/prevention of certain conditions. It was shown that polyphenols could be used both as protective/prophylactic compounds and as therapeutic compounds. A sufficient amount can be achieved either by consuming a diet, rich in polyphenols, or in the form of dietary supplements and nevertheless with formulations such as nutraceuticals. The health effects of polyphenols depend not only on the amount consumed but also on their bioavailability. However, their overconsumption can cause safety concerns due to the accumulation of these molecules in the body, especially considering that the regulatory legislation in the field of dietary supplements is rather loose. Therefore, this review focuses on the major positive effects of natural-derived polyphenols, and addresses potential safety concerns, with a focus on neuroprotection and neurotoxicity.